Bacillus coagulans MF-06 alleviates intestinal mucosal barrier from damage in chicks infected with Salmonella pullorum via activating the Wnt/β-catenin pathway - Ma, Li; Tian, Guangming; Pu, Yuejin; Qin, Xuguang; Zhang, Yinghu; Wang, Haojie; You, Lei; Zhang, Gaofeng; Fang, Chun; Liang, Xiongyan; Wei, Hongbo; Tan, Lei; et al. (Frontiers in Microbiology, 2024)
IntroductionThis study aimed to assess the protective efficacy of Bacillus coagulans MF-06 as a potential alternative to antibiotics in mitigating intestinal mucosal damage in chicks infected with Salmonella pullorum.MethodsA total of 150 one-day-old SPF chicks were selected and randomly divided into five groups: control group (CK), probiotics group (EM), probiotics treatment group (PT), antibiotic treatment group (AT), Salmonella pullorum group (SI), CK, AT and SI groups were fed a basal diet, EM and PT groups were fed a basal diet supplemented with 1.0 × 108 CFU/g Bacillus coagulans; PT, AT and SI groups were gavaged with 1.0 × 109 CFU/0.5 mL Salmonella pullorum at 7 days of age; AT group were fed with 0.375 g/kg neomycin sulfate in the basal diet from days 7–14.ResultsSubsequently, the study evaluated alterations in growth performance, the integrity of the intestinal mucosal barrier, cytokines associated with the Wnt/β-catenin signaling pathway, and gut microbiota composition. The results revealed that the administration of Bacillus coagulans MF-06 significantly reduced the feed conversion ratio of chicks (p < 0.05), and significantly increased the average daily weight gain and average daily feed intake in chicks challenged with Salmonella Pullorum (p < 0.05). Furthermore, Bacillus coagulans MF-06 treatment diminished the presence of Salmonella pullorum colonies in the intestinal tract. Additionally, the administration of Bacillus coagulans MF-06 restored levels of (Diamine oxidase) DAO and (D-lactic acid) D-LA levels, as well as the levels of tight junction protein, including TJP1, CLDN1, CLDN2, Occludin, and MUC2 (p < 0.05). The study noted a significant decrease in cell apoptosis (p < 0.05) and a significant increase in the expression of Proliferating Cell Nuclear Antigen (PCNA) and v-myc avian myelocytomatosis viral oncogene homolog (C-MYC) (p < 0.05), which activated the Wnt/β-catenin signaling pathway. Analysis through 16S rRNA sequencing revealed that the intake of Bacillus coagulans MF-06 led to a significant decrease in the relative abundance of Lachnoclostridium, Shuttleworthia, and unidentified-Eggerthellaceae (p < 0.05).DiscussionCollectively, the Bacillus coagulans MF-06 may provide a protective effect against Salmonella pullorum infection in chicks by enhancing growth performance, strengthening the integrity of the intestinal mucosal barrier, and stabilizing the gut microbiota.